Measures of stored red blood cell quality. Issue 1 (22nd January 2014) - Hess, J. R.
<x xml:space="preserve">Abstract</x> Blood banking underpins modern medical care, but blood storage, necessary for testing and inventory management, reduces the safety and efficacy of individual units of red blood cells (RBCs). Stored RBCs are damaged by the accumulation of their own waste products, by enzymatic and oxidative injury, and by metabolically programmed cell death. These chemical activities lead to a complex RBC storage lesion that includes haemolysis, reduced in vivo recovery, energy and membrane loss, altered oxygen release, reduced adenosine tri‐phosphate and nitric oxide secretion, and shedding of toxic products. These toxic products include lysophospholipids that can cause transfusion‐related acute lung injury, free iron that can potentiate infections and cause inflammation, and shed microvesicles that can scavenge nitric oxide and potentiate inflammation and thrombosis. However, most of the obvious negative outcomes of RBC storage are uncommon and appear to be related to exceptionally bad units. Generally, the quality of stored RBCs is highly related to the conditions of storage, so refrigerator temperature, intact bags, residual leucocyte counts and visible haemolysis remain excellent general measures. Specific biochemical measures, such as adenosine 5′‐triphosphate (ATP) and 2, 3‐diphosphoglycerate (DPG) concentrations, calcium and potassium content or lipid breakdown products, require specialized measures that are not widely available, involve destructive testing and generally reflect only a part of the storage lesion. This review describes a number of components of the storage lesion and their measurement and attempts to access the utility of the measures.